2010
DOI: 10.3109/08860220903541135
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Proteinuria with Lercanidipine Associated with Renin-Angiotensin Axis-Blocking Drugs

Abstract: Objective. Most calcium antagonists do not seem to reduce microalbuminuria or proteinuria. We have tried to assess the antiproteinuric effect of a calcium channel blocker, lercanidipine, in patients previously treated with ACE inhibitors or angiotensin receptor blockers. Design and Methods. The study included 68 proteinuric (> 500 mg/day) patients (age 63.1 ± 12.9 years, 69.1% males and 30.9 females). All patients were receiving ACE inhibitors (51.4%) or angiotensin II receptor blockers (48.6%) therapy but had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
0
10
0
5
Order By: Relevance
“…ARB/ACE-I reduce intraglomerular pressure, which has a renoprotective effect, by inhibiting angiotensin II-mediated efferent arteriolar vasoconstriction. 16) There have been no reports on the additive or synergistic effects of tolvaptan and ARB/ACE-I in patients with HF. Perico, et al reported that a dual type 1a and 2 vasopressin receptor antagonist induced a partial antiproteinuric effect, which was enhanced by the addition of enalapril or losartan in a model of chronic proteinuric nephropathy in rats.…”
mentioning
confidence: 99%
“…ARB/ACE-I reduce intraglomerular pressure, which has a renoprotective effect, by inhibiting angiotensin II-mediated efferent arteriolar vasoconstriction. 16) There have been no reports on the additive or synergistic effects of tolvaptan and ARB/ACE-I in patients with HF. Perico, et al reported that a dual type 1a and 2 vasopressin receptor antagonist induced a partial antiproteinuric effect, which was enhanced by the addition of enalapril or losartan in a model of chronic proteinuric nephropathy in rats.…”
mentioning
confidence: 99%
“…В частности, у пациентов с АГ и са-харным диабетом была продемонстрирована большая эффективность такой комбинации, чем сочетания бета-адреноблокатора и иАПФ [52].…”
Section: дополнительные эффекты лерканидипинаunclassified
“…An action on both pre-and post-capillary vasodilatation may underlie the reduced clinical incidence of pedal edema, the most common side effect ofcalcium antagonists, seen with lercanidipine relative to other 1,4-dihydropyridines (19). Addition of lercanidipine to antihypertensive therapy with RAAS blocker leads to further benefits for renal function (10,11). Prescription of third generation CCBs is associated with improvements in adherence and persistence to antihypertensive therapy.…”
Section: At1 Receptor Blockers (Arb)mentioning
confidence: 99%